Effect of solution transition on steering the sales force : for new marketing and sales metrics - Schnerrer, Julien (Anchor Academic Publishing, 2014)
The objective of this study is to provide a metric that helps to assess the solution readiness status of a firm's sales force. Sales are often considered as part of a marketing strategy. It will be analyzed to what extent this perspective is justified and how this is influenced by the emergence of solutions. Besides, an overview about the sales marketing interface will be given to raise the awareness of this topic. Furthermore, this study will increase the understanding of the reader about applied metric concepts in marketing departments that can be found in existing firms today. It will be de.